ASSESSING STUDENTS’ ENGLISH PROFICIENCY THROUGH TOEFL TEST AT ANIMAL HUSBANDRY STUDENTS OF UNIKS - Gusparia, Gusparia; Gundary, Puspa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research was conducted to find out the students’ score in TOEFL test at Islamic University of Kuantan Singingi (UNIKS). The research design was the descriptive research. The population of this research was the fifth semester students at Animal Husbandry Program Study. The population was 18 students. The instrument used in this research was a multiple choice test which is consisted of three assessment sections namely, Listening Comprehension (section 1), Structure & Written Expression (section 2), and Reading Comprehension (section 3). Based the research data, students' score in TOEFL test was in elementary level. It was classified as the lowest level in TOEFL test. The students only reached the range around 310-420. There were six students who got score above 400. Only one student got the highest score 433 and one student got the lowest score of 317. There were about six students who scored below 400 to 350. Around six students who got a score below 350. The finding indicated that the students’ had less experience in TOEFL and they lacked knowledge of grammar in English. In this case, students should have more practice and preparation before taking TOEFL test.Keywords: Assessing, English Proficiency, TOEFL test